Introducing Progressive Strength Training Program in Singapore's Elder Care Settings - Björkgren, Magnus; Borg, Frank; Tan, Ken; Laxåback, Gerd; Nygård, Lisette (Frontiers in Medicine, 2021)
The use of progressive strength training among the elderly has become an accepted part of evidence-based practice for preventive and rehabilitative care. Exercise is undoubtedly one of the pillars for resilient aging. While research has shown impressive outcomes from strength training, the challenge remains to get elderly persons to exercise. Here we describe a Finnish-Singaporean cross-national project that provides a unique opportunity to evaluate the implementation of strength training in settings where it had previously not been applied. We report from the first two years of implementation using assessment data and surveys directed to frontline therapists responsible for the implementation. The strength training concept was progressively implemented in 24 elder care locations in Singapore including residential homes, day rehab/care centres, and senior activity centres. Each location was provided with training, support, gym equipment and technology solutions. It remained for individual sites to enroll elderly to the program, to perform assessments, and to direct the progressive strength training. Based on data from the first two years of implementation, improvements in lower body muscle strength were found in Leg Curl (ave 11.1-48.8%), Leg Extension (ave 10.2-24.0%) and Hip Abduction/Hip Adduction (ave 7.0-15.8%). Of the trained therapists, 95% strongly agreed or agreed to some extent that the implementation had been successful. The practice-based evidence from the project has demonstrated that it is feasible to implement progressive strength training in real life settings, using technology. While the implementation initially required handholding and support, the approach yielded consistent improvement rates in muscle strength comparable to results from randomized clinical trials (meta-analysis studies). Significant improvement rates in muscle strength were found in all three types of sites, demonstrating that gym training can be employed broadly in elder care. The Senior Activity Centers offer an interesting model for reaching seniors with preventive actions at an early stage. The data support a 3-month training as an effective intervention of introducing strength training in elder care settings, promoting healthy aging.